Math Archive (14)

Calculus Level 5

Find the area between the curves y = x 2 + x 2 y=x^{2}+x-2 and y = 2 x y=2x for which x 2 + x 2 + 2 x = x 2 + 3 x 2 |x^{2}+x-2|+|2x|=|x^{2}+3x-2| .


This is a submission to Problem Writing Party May 2016.
7 2 \frac{7}{2} 7 6 \frac{7}{6} 14 3 \frac{14}{3} 7 3 \frac{7}{3}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Given that { y = x 2 + x 2 . . . ( 1 ) y = 2 x . . . ( 2 ) \begin{cases} y = x^2 + x - 2 &...(1) \\ y = 2x & ...(2) \end{cases}

( 1 ) = ( 2 ) : x 2 + x 2 = 2 x x 2 x 2 = 0 ( x + 1 ) ( x 2 ) = 0 \begin{aligned} (1)=(2): \quad x^2+x-2 & = 2x \\ x^2 - x - 2 & = 0 \\ (x+1)(x-2) & = 0 \end{aligned}

Therefore, the bound area by y = x 2 + x 2 y = x^2 + x - 2 and y = 2 x y = 2x is between 1 x 2 -1 \le x \le 2 . We need to find the range of x x that satisfies x 2 + x 2 + 2 x = x 2 + 3 x 2 |x^2+x-2|+|2x|=|x^2+3x-2| . Let us consider the L H S LHS of the equation.

x 2 + x 2 + 2 x = ( x + 2 ) ( x 1 ) + 2 x = { x 2 + x 2 + 2 x = x 2 + 3 x 2 = R H S for x 1 ( x 2 + x 2 ) + 2 x = x 2 + x + 2 R H S for 0 x < 1 ( x 2 + x 2 ) 2 x = ( x 2 + 3 x 2 ) = R H S for 2 x < 0 \begin{aligned} |x^2+x-2|+|2x| & = |(x+2)(x-1)|+|2x| \\ & = \begin{cases} x^2+x-2+2x = x^2+3x-2 = RHS & \text{for }x \ge 1 \\ -(x^2+x-2) + 2x = -x^2+x+2 \ne RHS & \text{for }0 \le x < 1 \\ -(x^2+x-2) - 2x = \color{#3D99F6}{- (x^2+3x-2) = RHS} & \text{for } -2 \le x < 0 \end{cases} \end{aligned}

Note that for 2 x < 0 -2 \le x < 0 , x 2 + 3 x 2 < 0 ( x 2 + 3 x 2 ) = x 2 + 3 x 2 = R H S \color{#3D99F6}{x^2+3x-2} < 0 \implies \color{#3D99F6}{- (x^2+3x-2) = |x^2+3x-2| = RHS } .

Therefore, the ranges of x x that satisfy x 2 + x 2 + 2 x = x 2 + 3 x 2 |x^2+x-2|+|2x|=|x^2+3x-2| are 1 x 0 -1 \le x \le 0 and 1 x 2 1 \le x \le 2 and the area bounded by the ranges is:

A = 1 0 ( x 2 + x 2 2 x ) d x + 1 2 ( x 2 + x 2 2 x ) d x = 1 0 ( x 2 x 2 ) d x + 1 2 ( x 2 x 2 ) d x = x 3 3 x 2 2 2 x 1 0 + x 3 3 x 2 2 2 x 1 2 = 0 7 6 + 20 6 + 13 6 = 7 6 + 7 6 = 7 3 \begin{aligned} A & = \left| \int_{-1}^0 \left(x^2+x-2 - 2x \right) dx \right| + \left| \int_1^2 \left(x^2+x-2 - 2x \right) dx \right| \\ & = \left| \int_{-1}^0 \left(x^2-x-2 \right) dx \right| + \left| \int_1^2 \left(x^2-x-2 \right) dx \right| \\ & = \left| \frac{x^3}{3} - \frac{x^2}{2} - 2x \bigg|_{-1}^0 \right| + \left| \frac{x^3}{3} - \frac{x^2}{2} - 2x \bigg|_1^2 \right| \\ & = \left| 0 - \frac{7}{6} \right| + \left| -\frac{20}{6} + \frac{13}{6} \right| \\ & = \frac{7}{6} + \frac{7}{6} = \boxed{\dfrac{7}{3}} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...